Manufacturing Consent in Video Games: The Hegemonic Memory Politics of «Metal Gear Solid V: The Phantom Pain» (2015) - Hammar, Emil Lundedal (Nordlit, 2019)
In this article I argue that the structural conditions of global capitalism and postcolonialism encourage game developers to rearticulate hegemonic memory politics and suppress subaltern identities. This claim is corroborated via an application of Edward Herman and Noam Chomsky’s propaganda model to the Japanese-developed video game Metal Gear Solid V: The Phantom Pain. This case study highlights that the hegemonic articulations of colonial histories are not exclusive to Western entertainment products where instead modes of production matter in the ‘manufacturing of mnemonic hegemony’. I also propose that the propaganda model, while instructive, can be improved further by acknowledging a technological filter and the role of the subaltern. Thus, the article furthers the understanding of the relation between production and form in contemporary technological phenomena like video games and how this relation motivates hegemonic articulations of the past in contemporary mass culture.